Fulminant hepatic failure caused by tuberculosis. Issue 5 (May 1995) - Hussain, W; Mutimer, D; Harrison, R; Hubscher, S; Neuberger, J
Abstract : A 54 year old Asian woman developed fulminant hepatic failure followed by renal failure. Because of a past history of possible tuberculosis, she was given antituberculous drugs. The chest x ray was normal. A transjugular liver biopsy showed caseating necrosis, granulomas, and acid fast bacilli indicative of miliary tuberculosis. Despite full supportive therapy, her condition deteriorated and she died. Postmortem examination showed widespread miliary tuberculosis; culture confirmed the presence of Mycobacterium tuberculosis. Tuberculosis causes fulminant hepatic failure rarely and only three cases have been described. In this, as with the other cases, hyponatraemia and hepatomegaly were features at presentation. This is the first report of treatment being given before death.